Systematic evaluation of evidence on veterinary viscoelastic testing Part 4: Definitions and data reporting. (January 2014) - Hanel, Rita M.; Chan, Daniel L.; Conner, Bobbi; Gauthier, Vincent; Holowaychuk, Marie; Istvan, Stephanie; Walker, Julie M.; Wood, Darren; Goggs, Robert; Wiinberg, Bo
Abstract Objective To systematically examine evidence surrounding definitions and reporting of data for viscoelastic testing in veterinary medicine. Design Standardized, systematic evaluation of the literature, categorization of relevant articles according to level of evidence and quality, and development of consensus on conclusions for application of the concepts to clinical practice. Setting Academic and referral veterinary medical centers. Results Databases searched included Medline, CAB abstracts, and Google Scholar. Conclusions All 4 standard thromboelastography (TEG) and rotational thromboelastometry (ROTEM) variables should be universally reported, and the reporting of shear elastic modulus in addition to maximum amplitude (MA) is encouraged. There is insufficient evidence to support universal usage of the coagulation index at this time. The K value and clot formation time are the most variable of the 4 parameters, with alpha angle, MA, and maximum clot firmness generally the least variable. Individual studies should report sufficient data on patients and institutional controls to enable definitions of hypo‐ and hypercoagulability to be evaluated post‐hoc, and it is recommended that all studies specifically report how these conditions were defined. In reporting data relating to fibrinolysis, the TEG variables LY30, LY60, CL30, CL60, and the ROTEM variables LI30, LI60, ML, LOT, and LT should be documented. Studies should report sufficient data on patients and controls to enable definitions of hyper‐ and hypofibrinolysis to be evaluated post‐hoc, and we suggest that standard TEG/ROTEM assays may be unable to detect hypofibrinolysis in companion animals. We recommend that every center establish reference intervals, which are specific to either TEG or ROTEM. These reference intervals should be established using veterinary clinical pathology guidelines, standardized protocols, and a minimum of 40 healthy animals. There are currently insufficient data in companion animals to suggest a utility for Vcurve variables beyond that of standard TEG variables.